Teori Dekonstruksi dalam mengintepretasi limbah ban kendaraan bertransformasi menjadi produk kursi sebagai makna baru - Deviyani, Ni Kadek Siska; Mudra, I Wayan (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
The use of used vehicle tire waste which can generate profits in everyday life is an interesting discussion regarding the application of tire demolition material as one of the furniture elements in its application to interior design using Derrida's theory of deconstruction. This paper aims to discuss the process of deconstructing furniture in interior design. This paper is aimed at examining the theory of deconstruction in order to transform the meaning of an object from a four-wheeled vehicle tire. The research method used is descriptive qualitative, while the data collection methods used are online observation, online documentation and library search with a semiotic approach in interpreting the research object in the aspect of material exploration furniture deconstruction. The main literature refers to the Semiotic Language Philosophy Book by Prof. Dr. Kaelan and the theory of deconstruction by the philosopher Jacques Derrida. The results of research on semiotic studies with the theory of deconstruction that transform meaning by Derrida resulted in the conclusion that vehicle tire waste can be transformed by means of deconstruction theory by destruction and then reconstruction so as to produce a new meaning in the tire waste into a furniture stool in its application. This renewal can occur because of the transformation of the meaning of a four-wheeled vehicle tire that is damaged (damaged) resulting in a used tire whose meaning is reconstructed into a stool.